( the effect of Cognitive Acceleration strategy and random excitement strategy in achievement of geography material and developing the reflective thinking for students of literary fifth class) (Journal Of Educational and Psychological Researches, 2016)
The research aims to find out the effect of Cognitive Acceleration strategy and random excitement strategy in achievement of geography material and developing the reflective thinking for students of literary fifth class .    the researcher depended a partial control experimental design with the three groups(the competence groups of the pre & post tests), The sample is deliberately selected  from first AL-Rusafah Directorate General of Education in Baghdad.  AL.fardoos Intermediate school for girls is the assigned school for  the experimental work. The research sample consisted of (102) student the randomly distributed on three groups; (A)is assigned the first experimental group contained(34)student and(c) is assigned the second experimental group (33)student and(b) is assigned the control group contained(35)student  .    The researcher matched the three groups in many variables ; prior knowledge ,age , IQ , achievement in geography for the previous year ,reflective thinking.         The teaching material is specified that contained the first three chapters of natural geography book for the fifth class of literary department for academic year (2014-2015) The researcher analysis Content material formulated behavioral objectives according to bloom classification for cognitive domain with its five levels , and in the light of the  behavioral objectives and material Content . (Twenty seven) lesson plans are prepared per group from three groups .Two tests are constructed ,the first one is for Achievement including (40) test items (31)objective items of multiple choice type,(9)items of essay type ,while the second test is for  reflective thinking skills including (40) test items ,after three months the researcher applied both of the post achievement test and reflective thinking and by using one-way ANOVA and Scheffe test ,the result were as follows  : There are not statistically significant difference on level of significance of (0,05 ) between the average score of first experimental group which studied Cognitive Acceleration strategy and the average score of second experimental group which studied random excitement strategy in Achievement test and reflective thinking test . There are not statistically significant difference on level of significance of (0,05) between the average score of first experimental group which studied Cognitive Acceleration strategy and the average score of control group which studied the traditional method in Achievement test. There are statistically significant difference on level of significance of (0,05) between the average score of first experimental group which studied Cognitive Acceleration strategy and the average score of control group which studied the traditional method in reflective thinking test and the result was sided with first experimental group . There are statistically significant difference on level of significance of (0,05) between the average score of second experimental group which studied random excitement strategy and the average score of control group which studied the traditional method in Achievement test and reflective thinking test and the result was sided with second experimental group.           In the light of the above stated results, suitable conclusions, recommendations, and suggestions for further studies are put forward.